Beginning of the end of Onchocerciasis in the Americas (Colombia Medica, 2013)
Onchocerciasis, also known as River Blindness, is a parasitic disease caused by the nematode Onchocerca volvulus and transmitted by black flies of the genus Simulium. It is endemic in Africa, where an estimated 37 million people are infected. It is almost certain that the slave trade in the 17th and 18th centuries brought onchocerciasis from West Africa to the Americas (1),  where transmission foci  where established  in  six  countries: Mexico, Guatemala, Venezuela,  Brazil, Ecuador  and Colombia.  Since the beginning of the 20th century it was suspected that this vector borne disease was present in Colombia but the first confirmed case was not reported until 1965. The exact location of the single focus in the country was confirmed almost thirty years later in the locality of Naicioná, on the stream that bears the same name